DETERMINACIÓN DEL RIESGO DE EROSIÓN HÍDRICA DE SUELOS DE LOS DEPARTAMENTOS MINAS Y CHOS MALAL (NEUQUÉN) MEDIANTE LA APLICACIÓN DE LA ECUACIÓN UNIVERSAL DE PÉRDIDA DE SUELO (USLE) - Laurentino Hernandez; Ana C. Dufilho (Boletín Geográfico)
Soil erosion is one of the greatest environmental problems in semi-arid. 35.0 % of the Patagonia suffers from degradation mainly due to livestock, having sectors with a few probability of recovery. The study area (10,500 km2), includes Minas and Chos Malal Departments in northern of Neuquén Province, where livestock transhumance is practiced by nearly 1,500 families as their main economic activity. In this paper we estimated the potential loss of soil by water erosion under different land management scenarios, using Universal Soil Loss Equation and a Geographic Information System. The results indicated that 45.6% of the surface presented minor water erosion (<10 tons / ha / year), by 21.5% corresponded to high erosion (50-200 tonnes / ha / year) and 3.6% of the land was affected by current potential erosion loss, greater than 200 tonnes / ha / year.